Bed agglomeration characteristics of rice straw combustion in a vortexing fluidized-bed combustor. (May 2015) - Duan, Feng; Chyang, Chien-Song; Zhang, Li-hui; Yin, Siang-Fong
Highlights: Combustion of rice straw was conducted in a VFBC to study bed agglomeration behavior. Eutectics with low melting point materials promote defluidization at high temperatures. The alkali concentration has the highest value at the upper bubbling zone. Coal ash inhibits the formation of low melting compounds of rice straw combustion. Abstract: To investigate bed agglomeration characteristics, the combustion of pelletized rice straw was conducted in a bench-scale vortexing fluidized bed. Effects of bed temperature, superficial velocity, secondary gas velocities, and mass blended ratio of coal on the defluidization time were investigated. The alkali concentrations in different sections of the bed zone were also studied. The bed materials and agglomerates were analyzed using SEM/EDX to obtain the surface morphology and the compositions. The results revealed that the defluidization time is increased with superficial gas velocity and is decreased with bed temperature. Eutectic composition with low melting point materials promote defluidization at high temperatures. Effect of the secondary gas velocity on the defluidization time indicates different trends at different bed temperatures. The highest value of alkali concentration appears at upper bubbling zone. Coal ash can avoid the existence of a certain eutectic composition, and increases its melting point.